Evolution of the locomotor skeleton in Anolis lizards reflects the interplay between ecological opportunity and phylogenetic inertia - Feiner, Nathalie (Nat Commun, 2021)
Anolis lizards originated in continental America but have colonized the Greater Antillean islands and recolonized the mainland, resulting in three major groups (Primary and Secondary Mainland and Greater Antillean). The adaptive radiation in the Greater Antilles has famously resulted in the repeated evolution of ecomorphs. Yet, it remains poorly understood to what extent this island radiation differs from diversification on the mainland. Here, we demonstrate that the evolutionary modularity between girdles and limbs is fundamentally different in the Greater Antillean and Primary Mainland Anolis. This is consistent with ecological opportunities on islands driving the adaptive radiation along distinct evolutionary trajectories. However, Greater Antillean Anolis share evolutionary modularity with the group that recolonized the mainland, demonstrating a persistent phylogenetic inertia. A comparison of these two groups support an increased morphological diversity and faster and more variable evolutionary rates on islands. These macroevolutionary trends of the locomotor skeleton in Anolis illustrate that ecological opportunities on islands can have lasting effects on morphological diversification.